Searching for the Mechanisms of Mammalian Cellular Aging Through Underlying Gene Regulatory Networks - Li, Wenbo; Zhao, Lei; Wang, Jin (Frontiers in Genetics, 2020)
Ageing attracts the attention throughout the history of humankind. However, it is still challenging to understand how the internal driving forces, for example, the fundamental building blocks of life such as genes and proteins, as well as the environments work together to determine longevity in mammals. In this study, we built a gene regulatory network for mammalian cellular ageing based on the experimental literature and quantify its underlying driving force for the dynamics as potential and flux landscape. We found three steady state attractors: fast-ageing state attractor, slow-ageing state attractor and intermediate state attractor. The system can switch from one state attractor to another driven by the intrinsic or external forces through the genetics and the environment. We identified the dominant path from the slow-ageing state directly to fast-ageing state. We also identified the dominant path from slow-ageing to fast-ageing through an intermediate state. We quantified the evolving landscape for revealing the dynamic characteristics of ageing through certain regulation changes in time. We also predicted the key genes and regulations for fast-ageing and slow-ageing through the analysis of the stability for landscape basins. We also found the oscillation dynamics between fast-ageing and slow-ageing and showed that more energy is required to sustain such oscillations. We found that the flux is the dynamical cause and the entropy production rate is the thermodynamic origin of the phase transitions or the bifurcations between the three state phase and oscillation phase. The landscape quantification provides a global and physical approach to explore the underlying mechanisms of cellular ageing in mammals.